Total Physical Response (TPR) Method to Improve Speaking Ability to Children with Down Syndrome - Yanti, Maya Damai; Rochyadi, Endang; Sunardi, Sunardi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Speaking and language skills are tools used to interact and communicate. Down syndrome children experience language development delays due to the impact of intelligence barriers that are below average. However, children can still take part in academic learning. The ability of children when learning to speak, especially speaking, is influenced by the learning methods used by the teacher. This study aims to (1) describe the current condition of the subject. (2) this method of practicing speaking skills is used. (3) Total Physical Response (TPR) method. This study used qualitative research methods. Data collection was carried out by observation, interviews, and documentation. Data analysis begins with studying data, data reduction, data presentation, and the stage of concluding. Subjects in this study were Down syndrome children aged 7 years who were unable to speak.